Factors Associated With Undernutrition among Persons Living With HIV in Kiziguro Catchment Area, Rwanda - Clotilde, Mukaniyongoma; Nwanna, Kevin (Journal of Health, Medicine and Nursing, 2025)
Purpose: HIV infection is really a serious problem as it accompanied by undernutrition in most of the cases. Many study was done in Rwanda about undernutrition but they didn’t focus on undernutrition among HIV infected persons, therefore the study is aimed to determine the factors associated with malnutrition among persons living with HIV in Rwanda with case study of KIZIGURO area. Methodology: The study was used quantitative approach for cross –sectional design to get data from persons living with HIV in each health facilities in Kiziguro District Hospital. A simple random sampling was used. Yamen formula was used to estimate to get a sample size for participants for this study. The adult infected persons of 15 years old and above in in Kiziguro area is 5036 by hmis data of April 2024 and to sample data to be used , the formula used is Yamen which is approximately 371 participants to be sampled for using in this study. And to sample for each health facility stratified random sampling is used A questionnaire was used as data collection instrument. SPSS (Statistical Package in Social Science) was used for data analysis. A study used a primary data collected from medical records such as BMI, CD4,Viral loads even the clients experience TB, Diarrhea, social economic and demographic factors about the clients living with HIV. Data was presented inform of table and figures. Findings: The results from the study demonstrated that 9.2% with95% CI (6.3%- 12.1%)of the adults persons with HIV positive were under nourished while 90.8% with 95%CI(87.9%-93.7%)of adults with HIV positive were not under nourished. In addition to this result The result from this study found that there is an odd of malnutrition within person living with HIV who screened positive for TB 13.682 times higher than an odd of not malnourished person living with HIV who didn’t screened positive for TB(AOR=3.682,95%CI:[3.618-51.745], p-value < .0001). Also there is an odd of malnutrition (under nutrition) within persons living with HIV who diagnosed for diarrhea is 13.036 times higher than the group of persons without malnutrition (under nutrition) who don’t diagnosed for diarrhea AOR=13.036,95%CI:(4.239- 40.086). And an odd of malnutrition (under nutrition) within persons living with HIV who have no level of education is 0.088 times less than the odd of group of all persons who has level of education who don’t have malnutrition(undernutrition) but living with HIV, AOR=0.088,95%CI (0.1-0.786) P value 0.03. Additionally educational level, means of transport to health facility to take anti retro therapy, place of residence, ever screened positive for TB, ever diagnosed for diarrhea were found to be significantly associated with undernutrition among persons living with HIV. These findings are found to be underscore to association between them and undernutrition situation, such as age, gender, marital status, house hold size, employment status, type of health facility, time spending in taking anti retro viral treatment, WHO clinical stage, recent viral load count, recent CD4 count. Unique Contribution to Theory, Practice and Policy: The results from the study are going to be used by decision makers such as Ministry of health to enhance living of HIV-infected peoples.